Penerapan Metode Pembelajaran Jigsaw dalam Meningkatkan Minat Belajar Siswa pada Pendidikan Agama Katolik - Sergius Lay; Hildegardis Dwinag Angelita Lahagu; Betty Novriani Zebua; Martina Rosmaulina Marbun; Antonius P Sipahutar; Linda Kurniawati Waruwu (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2026)
This research aims to describe the application of the Jigsaw learning method in increasing students' interest in learning in Catholic Religious Education. This research is based on the fact that the application of monotonous teaching methods tends to result in low student engagement in the learning process, which in turn affects their interest in learning. In this context, the Jigsaw method is viewed as one of the cooperative learning alternatives that can encourage students learn actively, responsibly, and collaboratively in groups. In this study, a qualitative descriptive approach was used through a literature review. Data were obtained through the study various relevant bibliographic sources, and then analysed descriptively through the stages of collection, selection, classification, interpretation, and conclusion drawing. The research shows that the Jigsaw learning method can increase students' interest in learning, as this method encourages students to be more active in the learning process, more responsible in understanding and conveying the material, and more capable of collaborating with their peers. The Jigsaw method also contributes to the creation of a more dynamic, participatory, and meaningful learning atmosphere. Therefore, the Jigsaw learning method is a strategic alternative that should be implemented to improve the quality of Catholic Religious Education.